Engineered Customizable Microvessels for Progressive Vascularization in Large Regenerative Implants. Issue 4 (28th November 2021) - Li, Cuidi; Han, Xiaoyu; Ma, Zhenjiang; Jie, Tianyang; Wang, Jinwu; Deng, Lianfu; Cui, Wenguo
Abstract: Inspired by the rapid angiogenesis of natural microvessels in vivo, engineered customizable microvessels (ECMVs) are developed which can naturally angiogenic sprout and induce vascular network formation via combing a celluar coaxial microfluidic extrusion technique with microsurgery post‐process. ECMVs can be used for customization of primarily pre‐vascularized soft tissue regenerative implants with personalized shape and vascular density with the aid of sacrificial printing technology. After collaborating with surrounding cells, ECMVs angiogenic sprouted and formed daughter vascular networks. Through techniques such as injection and suturing, ECMVs can also be introduced into large bone repair implants for pre‐vascularization and osteogenesis promotion. Furthermore, the microvessel networks with personalized shapes are customized by connecting the coaxial microfluidic system to a 3D printer. It is further demonstrated that the vascularization promotion and anastomose with host vessels of the ECMVs in vivo. Thus, ECMVs provide a simple engineering strategy for rapid vascularization of clinically large regenerative soft/hard tissue implants. Abstract : Engineered customizable microvessels with sprouting angiogenesis potential are fabricated to promote rapid vascularization of regenerative scaffolds after implantation. With the combination of celluar coaxial microfluidic technology and a microsurgery post‐dissection treatment, ECMVs which can be introduced into a variety of soft/hard regenerative scaffolds are constructed.